Conservation implications of song divergence between source and translocated populations of the North Island Kōkako. Issue 4 (21st May 2013) - Valderrama, Sandra V.; Molles, Laura E.; Waas, Joseph R.; Slabbekoorn, Hans
Summary: Translocation of individuals from healthy source populations to newly colonize or recolonize suitable habitat is a vital tool for the conservation of a species. Demographic, genetic and landscape factors, but also acoustic signals and cultural factors, will all affect translocation success. We investigated variation in song, and response to song, of the endangered North Island kōkako Callaeas wilsoni (Bonaparte 1850) in New Zealand in two translocated populations and their source population. We found significant vocal variation between the source population and both translocated populations, the latter of which had reduced repertoire sizes and increased repertoire sharing, as well as structurally different song elements of higher frequency and shorter duration. Despite the song divergence and clear variability in the nature and level of response among populations, we did not find any evidence for discrimination against nonlocal song in our reciprocal playback experiments. Synthesis and applications . Vocal divergence and reduced variability in translocated populations suggest founder effects or reduced social interaction rates. The variation could be viewed as cultural erosion and may undermine translocation success. Persistence of response to playback, despite vocal divergence, suggested that social restrictions on gene flow require at least a few decades of separation after translocation. The decision to translocate individuals of threatened species is becoming a more common tool for species conservation world‐wide. We argue that it is important to take vocal variation into account during such management decisions as it may affect success of establishment and persistence of translocated populations. Abstract : Vocal divergence and reduced variability in translocated populations suggest founder effects or reduced social interaction rates. The variation could be viewed as cultural erosion and may undermine translocation success. Persistence of response to playback, despite vocal divergence, suggested that social restrictions on gene flow require at least a few decades of separation after translocation. The decision to translocate individuals of threatened species is becoming a more common tool for species conservation world‐wide. We argue that it is important to take vocal variation into account during such management decisions as it may affect success of establishment and persistence of translocated populations.